Determinants of Application of Research Methodologies in Architecture Programs in Covenant University, Ota, Nigeria - Aderonmu, Peter A. (International Journal of Innovative Technology and Exploring Engineering, 2020)
Research methodologies (R.Ms) employed in carrying out studies have been found in diverse contexts to influence the outcome. This study examined the determinants of applications of R.Ms in undergraduate and postgraduate studies in Department of Architecture Covenant University Ota, Nigeria. The objectives include analysis of the identified R.Ms attributes and identification of the factors influencing applications of the R.Ms employed in architecture research programs (B.Sc., M.Sc., and M.Phil./Ph.D Degrees) in the University. The methodology adopted for the work is the cross-sectional survey of the 153 final year B.Sc., the M.Sc., and the Ph.D Students using 5-point Likert Scale questionnaire as data collection instruments; and interview of 16 of the students across the levels. Data obtained from the survey; and interview of the students were subjected to descriptive statistics (percentages and frequencies) and inferential statistics (Kruskal-Wallis Test, Linear multiple regression and Cross-tabulation). The results showed that Level/Program (.428), Rating of appropriateness of methodology for current or terminal research (.046), Gender (.044), Type of terminal research (.040), Distance of Residence to Department (.023), are the principal five (5) of the 13 predictors of the dependent variable in the study (representing 72.99% of total contribution to the model with R Square of .796).The study recommended commencement of ‘research methodology course’ which used to be in 400 Level Alpha to be moved from 300 Level Omega to 200 Level Alpha and Omega for early higher mastery, and for supervisors to consciously ensure more applications of R.Ms at undergraduate level beginning from 200 Level. Also female students are to apply quantitative RM more than their usual practice even from early part of undergraduate level.